Burnout and Risk of Cardiovascular Disease Evidence, Possible Causal Paths, and Promising Research Directions. [article]. - Melamed, Samuel
Burnout is characterized by emotional exhaustion, physical fatigue, and cognitive weariness, resulting fro prolonged exposure to work-related stress. The authors review the accumulated evidence suggesting that burnout and the related concept of vital exhaustion are associated with increased risk of cardiovascular disease and cardiovascular related-events. The authors present evidence supporting several potential mechanisms linking burnout with ill health, including the metabolic syndrome, dysregulation of the hypothalamic-pituitary-adrenal axis along with sympathetic nervous system activation, sleep disturbances, systematic inflammation , impaired immunity functions, blood coagulation and fibrinolysis, and poor health behaviors. The association of burnout and vital exhaustion with these disease mediators suggests that their impact on health may be more extensive than currently indicated. -- (from the author)